DIGITAL MARKETING STRATEGIES FOR CULINARY MSMEs THROUGH TIKTOK AND INSTAGRAM - Budi Safatul Anam; Hendri Mauliansyah (GREET, 2025)
This study examines effective digital marketing strategies for culinary micro, small, and medium enterprises (MSMEs) through TikTok and Instagram, addressing critical gaps in current literature. While Instagram’s visual marketing and influencer collaborations are well-documented, TikTok’s potential for culinary MSMEs remains underexplored. Furthermore, existing studies often prioritize large corporations, overlooking the resource constraints, cultural narratives, and analytics utilization challenges faced by smaller businesses. This research employs a mixed-methods approach, combining semi-structured interviews with 200 culinary MSME owners and quantitative analysis of social media engagement data. Qualitative findings highlight the significance of culturally grounded storytelling, user-generated content, and micro-influencer collaborations in building brand authenticity and trust. Quantitative results indicate that TikTok excels in rapid engagement, with average engagement rates surpassing Instagram, while Instagram demonstrates stronger performance in long-term visibility and conversion through integrated shopping features. Analytics-driven decision-making emerged as a key factor in optimizing content performance, yet many MSMEs lack the skills to effectively interpret and act on these insights. The study proposes a comprehensive framework for digital marketing effectiveness that extends beyond surface-level metrics to include customer retention, repeat purchases, and revenue growth. These findings contribute to both academic discourse and practical guidance, offering MSMEs actionable strategies to leverage platform-specific strengths, integrate cultural storytelling, and utilize analytics for sustainable growth. By aligning content creation with platform algorithms and audience preferences, culinary MSMEs can remain competitive in an increasingly digital and dynamic market environment.